SEASONAL CHANGES IN THE BIOCHEMICAL COMPOSITION OF MUSCLES IN RELATION TO BREEDING CYCLE IN CARP MINNOW, SALMOSTOMA BACAILA (HAM.) FROM HIMAYATHSAGAR RESERVIOR, HYDERABAD - PISKA, RAVI SHANKAR; KUMAR, ARVIND (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1989)
Seasonal variations in the moisture, lipid, protein and glycogen contents in muscles of carp minnow, S bacaila (Ham) in relation to spawning cycle has been worked out. The muscles contain high moisture during immature and spent conditions and minimum during peak spawning period. The lipid, protein and glycogen values are high during prespawning and low at the time of spawning period. Lipid, protein and glycogen contents are found to be inversely proportional to the moisture and directly proportional to each other.